If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8c + -4c = 0 Combine like terms: -8c + -4c = -12c -12c = 0 Solving -12c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-12'. c = 0 Simplifying c = 0
| 37-4x=13-10x | | -7x+27=6(x-2) | | -12n=-60 | | -3x+11=x-9 | | 2=17(3)-4(b) | | 5x-8x-y+12x= | | x=-1.6+0.4y | | X^18=4 | | 5p+3=38 | | x+15+3=18 | | 52g-16g*3=40 | | -3n=-51 | | 2g+5=27 | | 5x=-116 | | 75=3(6p-5) | | f(x)=5x^2+9x-2 | | 3y+2+2y+16=180 | | 8m+3=13 | | 3x+x^2-4x=0 | | -8x-11=5 | | k-x=9 | | 4(b+4)=40 | | 20=5(3+c) | | 16=(-2v)+34 | | 10+3x=x+12 | | w+2c=77 | | 12=5+3n | | 2p+6=3p | | 7x-4=3x-16 | | 50+16/4= | | 6(6u-6)+5=59+6u | | 6(66u-6)+5=29+6u |